2003
DOI: 10.1242/dev.00393
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Wingless and Vestigial expression in wing and haltere discs ofDrosophila

Abstract: In the third thoracic segment of Drosophila, wing development is suppressed by the homeotic selector gene Ultrabithorax (Ubx) in order to mediate haltere development. Previously, we have shown that Ubx represses dorsoventral (DV) signaling to specify haltere fate. Here we examine the mechanism of Ubx-mediated downregulation of DV signaling. We show that Wingless (Wg) and Vestigial (Vg) are differentially regulated in wing and haltere discs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 48 publications
(64 reference statements)
1
21
0
Order By: Relevance
“…1C) based on immunolocalization of DE-Cad and ␤-catenin/Arm besides binding with fluorochrome conjugated Phalloidin to F-actin. Both ␤-catenin/Arm (Collins and Treisman, 2000;Jiang and Struhl, 1998;Prasad et al, 2003) and DE-Cad display characteristic upregulation across the DV boundary along the PD axis of wing imaginal disc ( Fig. 1D-DЈЈ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…1C) based on immunolocalization of DE-Cad and ␤-catenin/Arm besides binding with fluorochrome conjugated Phalloidin to F-actin. Both ␤-catenin/Arm (Collins and Treisman, 2000;Jiang and Struhl, 1998;Prasad et al, 2003) and DE-Cad display characteristic upregulation across the DV boundary along the PD axis of wing imaginal disc ( Fig. 1D-DЈЈ).…”
Section: Resultsmentioning
confidence: 97%
“…Following stocks were used: ft fd (ft 8 ) (Mahoney et al, 1991), ft 422 (Rawls et al, 2002), UAS-arm S10 , UAS-arm S2 (Pai et al, 1997), UAS-dsh (Neumann and Cohen, 1996), UAS-DE-Cad (Greaves et al, 1999), UAS-tcf⌬N (van de Wetering et al, 1997), UAS-ft (Matakatsu and Blair, 2004), UAS-GPI::DFz2 (Cadigan et al, 1998), N23-Gal4 (Prasad et al, 2003), vg-Gal4 (Simmonds et al, 1995). Q-vg-lacZ (Kim et al, 1996), BE-vg-lacZ (Williams et al, 1994) and fz…”
Section: Fly Stocks and Geneticsmentioning
confidence: 99%
“…Our analysis has identified all genes previously showed as direct Ubx targets in the haltere pouch as well as a large fraction of suspected Ubx targets: spalt, knot, blistered, and vestigial (17,(19)(20)(21); anachronism, CG16884, CG7201, CG8780, and CG11641 (27); the Egf receptor pathway components vein, rhomboid, and kekkon-1 (22); Cyp310a1, Delta, CG10990, CG5171, and E(spl)-C genes (26); and dally and dally-like (14,(23)(24)(25). Most of the targets identified in our microarray analysis have not been studied thoroughly in the context of wing or haltere development, but some of these genes have been reported in microarray studies and genetic screens (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular genetic studies have shown that many key patterning genes in the larval wing primordium are indeed regulated by Ubx, directly or indirectly, in the haltere primordium (14,17,(19)(20)(21)(22)(23)(24)(25). This finding has prompted the use of microarray expression profiling to systematically identify differentially expressed genes between wing and haltere imaginal discs (26,27).…”
mentioning
confidence: 99%
“…When both Sgg/ GSK-3b and hAPC are misexpressed together, human APC fails to sequester ARM/b-catenin (Bhandari and Shashidhara, 2001). This behavior has been validated in different genetic backgrounds of increased or decreased levels of Sgg/GSK-3b activity (Prasad et al, 2003;Bajpai et al, 2004). The previous observations suggest that at low levels of Sgg/GSK-3b activity, overexpressed hAPC binds and sequesters ARM/b-catenin, while at high levels of Sgg/GSK-3b activity, overexpressed hAPC binds and degrades ARM/b-catenin.…”
mentioning
confidence: 89%